Pemberdayaan Guru SD Gugus Srikandi dalam Implementasi Model Pembelajaran Inovatif Kurikulum Merdeka - Sri Sukaesih; Sri Ngabekti; Saiful Ridlo; Kartika Widyaningrum; Risa Dwita Hardianti; Sumardani (Universitas Negeri Semarang, 2025)
The “Merdeka Belajar” policy and Merdeka Curriculum, initiated by the Ministry of Education and Culture, represent a significant educational innovation in Indonesia. Gugus Srikandi, located in the Gunung Pati District, is an elementary school implementing the Merdeka Curriculum. However, several challenges persist in its implementation. Notably, 67% of teachers report the need for further strengthening in the use of interactive and meaningful learning models to achieve competency and the Profile of Pancasila Students. Observations indicate that teachers have received limited socialization related to the practical implementation of learning models. Furthermore, teachers' readiness to develop and evaluate learning activities with the curriculum still requires improvement. The objective of this initiative was to enhance teachers’ understanding of innovative learning models within the Merdeka Curriculum, as well as to empower them to design and implement active learning. The methodology of this activity involved several stages: needs analysis, program development, program implementation, observation and monitoring, and reflection and evaluation. The training and workshop activities were attended by 80 participants from elementary schools in the Gugus Srikandi. The results of the workshop indicate that teachers at Gugus Srikandi have developed strong pedagogical competencies in designing, implementing, and evaluating learning in accordance with the Merdeka Curriculum. Teachers are now able to apply innovative learning models to create active and contextual learning experiences